(untitled) (Global Journal of Science Frontier Research, 2017)
The biocosmological role of CP-symmetry-violating chiral Z 0 boson in the origin of the chiral life and the cosmological role of CP-symmetric Higgs boson H 0 in the inflationary origin of the matter-antimatter asymmetry in the semiclosed Friedman universe are discussed.